DEVIATION OF INTERPRETATION OF FETAL WEIGHT FOR BIRTHT WEIGHT - Wijayanti, Irfana Tri; Marfu?ah, Siti (LPPM STIKES KENDAL, 2020)
Estimated fetal weight is very important in making clinical decisions during pregnancy and childbirth. This helps the midwife predict the possibility of complications of childbirth pregnancy such as growth disturbance, macrosomia / large babies, CPD (Cephalopelvic disproportion) when labor progress is poor, or early detection of possible shoulder dystocia. Estimating fetal weight is an important task for midwives to be able to predict if there is a problem in newborns, so that knowing the estimated birth weight of a midwife will be able to make better labor preparation. The purpose of this study was to determine the level of accuracy of the formula for interpreting fetal weight for birth weight. This type of research is comparative research. The research method uses analytic survey with retrospective time approach. The population in this study was 40 TM III pregnant women, the total sampling technique. Measuring instruments using a questionnaire / research form. Data analysis using paired t test. Statistical test results using paired t test showed p value value 0.00 <0.05 which means there is a difference in interpretation of fetal weight according to Johson Tausak, Niswander, Risanto on the birth weight of babies. While the comparison test results show the calculated F value (7258)> F Table (3252) the mean value of Johson tausak 3350, Niswander 2757.14, Risanto 2986, 36 shows the formula of johnson tausak is closer to the facts.